Beneficial effects of ROCEN (Topical Nano-arthrocen) on atopic dermatitis in mice - Ramin Goudarzi; Maryam Eskandarynasab; Ahad Muhammadnejad; Ahmad Reza Dehpour; Alireza Partoazar (BMC, 2021)
Abstract Objective Atopic dermatitis (AD) is a chronic inflammatory skin disease mainly caused by immune stimuli. The current study was conducted to investigate the effects of ROCEN and to compare it with betamethasone (Beta) on mice subjected to AD. Methods First, the safety of topical ROCEN was tested to determine possible sensitization induction in vivo. Then, the mice were subjected to oxazolone (Oxa) to induce chronic AD. Consequently, they underwent treatment with ROCEN and Beta. Scratching and wiping behaviors related to dermatitis were evaluated in treated animals for 35 days. The histopathology and immunohistochemistry (IHC) analysis of interleukin-8 (IL-8) and tumor necrosis factor-α (TNF-α) cytokines were performed on the dorsal skin of the treated mice. Results Topical administration of ROCEN and Beta to the dorsum of sensitized mice for 5 weeks significantly alleviated scratching and wiping symptoms and reduced erythema, scaling, and edema in the skin of the mice with AD. Moreover, histological indices showed that ROCEN effectively reduced leucocyte infiltration and improved skin healing parameters in treated AD mice. Application of ROCEN or Beta reduced IHC markers including IL-8 and TNF-α significantly. Conclusion ROCEN alleviated the AD symptoms similar to betamethasone in an experimental animal model.